Effects of Deep Brain Stimulation on Postural Control in Parkinson's Disease. (July 2020) - Patel, Mitesh; Nilsson, Maria H.; Rehncrona, Stig; Tjernström, Fredrik; Magnusson, Måns; Johansson, Rolf; Fransson, Per-Anders
Abstract: The standard approach to the evaluation of tremor in medical practice is subjective scoring. The objective of this study was to show that signal processing of physiological data, that are known to be altered by tremor in Parkinson's disease (PD), can quantify the postural dynamics and the effects of DBS. We measured postural control and its capacity to adapt to balance perturbations with a force platform and perturbed balance by altering visual feedback and using pseudo-random binary sequence perturbations (PRBS) of different durations. Our signal processing involved converting the postural control data into spectral power with Fast-Fourier Transformation across a wide bandwidth and then subdividing this into three bands (0–4 Hz, 4–7 Hz and 7–25 Hz). We quantified the amount of power in each bandwidth. From 25 eligible participants, 10 PD participants (9 males, mean age 63.8 years) fulfilled the inclusion criteria; idiopathic PD responsive to l -Dopa; >1 year use of bilateral STN stimulation. Seventeen controls (9 males, mean age 71.2 years) were studied for comparison. Participants with PD were assessed after overnight withdrawal of anti-PD medications. Postural control was measured with a force platform during quiet stance (35 s) and during PRBS calf muscle vibration that perturbed stance (200 s). Tests were performed with eyes open and eyes closed and with DBS ON and DBS OFF. The balance perturbation period was divided into five sequential 35-s periods to assess the subject's ability to address postural imbalance using adaptation. The signal processing analyses revealed that DBS did not significantly change the dynamics of postural control in the 0–4 Hz spectral power but the device reduced the use of spectral power >4 Hz; a finding that was present in both anteroposterior and lateral directions, during vibration, and more so in eyes open tests. Visual feedback, which usually improves postural stability, was less effective in participants with PD with DBS OFF across all postural sway frequencies during quiet stance and during balance perturbations. The expected adaptation of postural control was found in healthy participants between the first and last balance perturbation period. However, adaptation was almost abolished across all spectral frequencies in both the anteroposterior and lateral directions, with both eyes open and eyes closed and DBS ON and OFF in participants with PD. To conclude, this study revealed that DBS altered the spectral frequency dynamics of postural control in participants through a reduction of the power used >4 Hz. Moreover, DBS tended to increase the stabilizing effect of vision across all spectral bands. However, the signal processing analyses also revealed that DBS was not able to restore adaptive motor control abilities in PD.